Pengembangan Sistem Informasi Manajemen Produksi Telur PT. Vega Nusa Argita berbasis Web (Studi Kasus : Desa Watukebo Kecamatan Rogojampi Banyuwangi) - Resya Futri Hadi Febryana; Adam Hendra Brata; Agus Wahyu Widodo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Vega farm is a business that is engaged in animal husbandry. Veg farms are focused on raising laying hens, where laying hens are a type of chicken that is specially raised for eggs. In one year laying hens can produce about 250-300 eggs. In vega farms, all production activities carried out must go through a process of recording that is useful as an evaluation material in the development of laying egg production for every day. However, the recording process carried out on vega fram farms is still done manually, namely the recording of data is still recorded using a book which is then transferred to Excel. Therefore, based on these problems, this research developed a web-based management information system that can help vega farms in managing production data of laying hens. This research uses the waterfall method in developing information systems which are implemented using the PHP programming language in the codeigniter framework. This system has been tested with the blackbox method for validation testing that produces 1115 test cases with 100% valid results, whitebox testing for unit testing, compatibility testing for testing non-functional requirements and based on the results of tests that have been carried out the system can run on different web browsers different.